Profiling elite male 100-m sprint performance: The role of maximum velocity and relative acceleration - Healy, R.; Kenny, I. C.; Harrison, A. J. (Journal of Sport and Health Science, 2022)
Purpose This study aimed to determine the accuracy of a 4 split time modelling method to generate velocity-time and velocity-distance variables in elite male 100-m sprinters and subsequently to assess the roles of key sprint parameters with respect to 100-m sprint performance. Additionally, this study aimed to assess the differences between faster and slower sprinters in key sprint variables that have not been assessed in previous work.